Study of Physical, Chemical, and Organoleptic Properties of Functional Drink Turkey Berry (Solanum torvum swartz) with the Addition of Butterfly Pea Flower (Clitoria ternatea linn) and Emprit Ginger (Zingiber officinale var. Amarum) - Anggriani, Rista; Putri, Nina Nurazizah Purnomo; Wahyudi, Vritta Amroini (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Turkey berry (Solanum torvum Swartz) is a wild plant often found in Indonesia and its usage is still limited. Turkey berry has a high potential as a source of antioxidants, which can be consumed as a functional drink. Ginger and butterfly pea flowers were selected as additional ingredients in composite drinks to enhance the quality of the functional drink in terms of function and sensory characteristics. This study aimed to determine the effects of variations in the concentration of turkey berry, butterfly pea flower, and ginger on the physical, chemical, and organoleptic characteristics. The design method used a Simple Randomized Block Design with four treatment combinations to be analyzed in three repetitions. Data were analyzed using Analysis of Variance (ANOVA) to determine the effects of the treatment. The results showed that turkey berry, in combination with ginger and butterfly pea flower, had a significant effect on the physicochemical and organoleptic characteristics, including pH, total phenolic content, total flavonoid content, antioxidants, color, aroma, taste, and preference.